Preimplantation genetic testing for familial amyloid polyneuropathy - Mário Sousa (BMC, 2022)
Abstract Background Embryo selection in Familial amyloid polyneuropathy eradicates the disease, but the widespread application of preimplantation genetic testing (PGT) for this monogenic disease still requires greater political and clinical commitment. Main body Familial amyloid polyneuropathy is a fatal, chronic, hereditary autosomal dominant neurodegenerative disorder caused by a single nucleotide mutation in the transthyretin gene. The disease courses with infertility, cachexia, blindness, renal failure, cardiovascular collapse, and premature death. Treatments include organ transplantation, transthyretin stabilizers, silencers and gene editing. Unfortunately, these treatments only improve the patient's quality of life. Short conclusion The application of PGT would prevent the disease, the birth of children with this devastating disease and the enormous health costs associated. For PGT to become the first reproductive option for patients, a paradigm shift in governmental, social and medical policies is necessary.